The misinterpretation of hadith texts by extremist groups to justify their terrorist acts: An analysis - Ahmad Shah, Faisal (Brill Academic Publishers, 2018)
This paper seeks to analyze the hadith texts which have been misinterpreted by various extremist groups to justify their terrorist acts. There were several narrations in the hadith that mention extremist acts in the past, such as the beheading of Abu Jahal by Ibn Mas'ud, the burning of enemies alive by Caliph Ali, and the presentation of the beheaded head of al-Aswad al-'Ansi to the Prophet PBUH. Unfortunately, these narrations were manipulated by extremist groups as their arguments to justify their extremist acts, without examining in depth the reasons why they occurred. This article aims to investigate the legitimacy of the stories, and find justification for the actions if they actually occurred. This paper uses qualitative research methodology by discussing hadith scholars' views and their interpretations of the jihad texts. The findings of the study show the extremist groups' dependency on the literal meaning of the hadith texts, and ignoring the context of the hadith. They also depend on weak hadiths that have been rejected by hadith scholars. Finally, this study outlines various ideas and suggestions to overcome confusion due to the misinterpretation of hadith texts by extremist groups.